The Correlation of Coping Stress and Social Support with Academic Stress on Distance Learning - Diana Lilik Kusumawati Dewi; Muslikah Muslikah (Bisma The Journal of Counseling, 2021)
This study discusses the correlation between coping stress and social support with academic stress in distance learning for 10th grade students of SMA Negeri in the District of Ngaliyan Semarang. The purpose of this study is to determine the relationship between variables and obtain information on the level of each variable with a sample of 255 students. The method in this research is ex-post facto quantitative. The results of the descriptive analysis showed that the level of stress coping of the tenth graders of SMA Negeri in Ngaliyan Semarang District was in the low category (M=2.56), the level of social support was high (M=3.04), and the level of academic stress in distance learning was high (M=2,67). The results of multiple regression analysis show that there is a negative and significant relationship between coping stress and academic stress in distance learning students (t=-10,854, =-0.646, p=<0.05), social support has no significant correlation. significant with academic stress on distance learning students (t=-0.908, =-0.054, p=>0.05), and there is a positive and significant correlation between stress coping and social support simultaneously on academic stress in distance learning students (R= 0.681; R²= 0.464; F=109.083, p=<0.05). Based on the results of the research, , it is hoped that the guidance and counseling teachers can provide guidance and counseling services to be able to reduce students' academic stress levels both individually and in groups, increase students' stress coping levels and services to maintain students' social support levels.